2020
DOI: 10.1038/s41467-020-19346-z
|View full text |Cite
|
Sign up to set email alerts
|

Revealing fine-scale spatiotemporal differences in SARS-CoV-2 introduction and spread

Abstract: Evidence-based public health approaches that minimize the introduction and spread of new SARS-CoV-2 transmission clusters are urgently needed in the United States and other countries struggling with expanding epidemics. Here we analyze 247 full-genome SARS-CoV-2 sequences from two nearby communities in Wisconsin, USA, and find surprisingly distinct patterns of viral spread. Dane County had the 12th known introduction of SARS-CoV-2 in the United States, but this did not lead to descendant community spread. Inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…Recent studies have also suggested that the intra-host heterogeneity of SARS-CoV-2 genome in individuals may be transferable (53)(54)(55), and given that a minuscule percent of population is responsible for most of the local transmission of SARS-CoV-2 infection (56-58), there arises a possibility of iSNVs harbouring genome to be passed through a super-spreading event. This, in an isolated population, might also lead to an altered haplotype with some unique variations leading to fixation or removal of alleles from the population (59). By temporally capturing iSNVs and the consequential variant appearance in the population, we could determine iSNV sites in the East Indian population which possibly transitioned into an SNV (Supplementary Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also suggested that the intra-host heterogeneity of SARS-CoV-2 genome in individuals may be transferable (53)(54)(55), and given that a minuscule percent of population is responsible for most of the local transmission of SARS-CoV-2 infection (56-58), there arises a possibility of iSNVs harbouring genome to be passed through a super-spreading event. This, in an isolated population, might also lead to an altered haplotype with some unique variations leading to fixation or removal of alleles from the population (59). By temporally capturing iSNVs and the consequential variant appearance in the population, we could determine iSNV sites in the East Indian population which possibly transitioned into an SNV (Supplementary Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…All consensus-level surveillance sequencing of SARS-CoV-2 was performed using Oxford Nanopore sequencing (n = 3,351) as described previously [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…We found that 24 (92%) of these 26 genomic sequences cluster tightly in the Nextstrain 20A clade on a time-resolved tree and are separated by 0-2 fixed consensus nucleotide differences (Figure 3). The limited diversity of viruses detected in the 24 individuals suggests sustained transmission of SARS-CoV-2 following a single introduction [20][21][22].Viruses from Athletics-3 and Athletics-26 did not appear to be part of the primary transmission cluster. As of 1-day-40, there was no evidence for onward spread within the program originating from Athletics-3 or Athletics-26.…”
Section: Resultsmentioning
confidence: 88%
“…All eight virus sequences (four from each team) clustered tightly in the 20G clade on a time-resolved tree and were separated by 0-2 fixed consensus nucleotide differences (Figure 4). Given the known epidemiological associations between these teams, this likely represented a single transmission cluster [20][21][22].…”
Section: Outbreak 2: Sars-cov-2 Transmission During Intercollegiate Cmentioning
confidence: 99%